CORRELATION ANALYSIS OF THE DEATH PENALTY ON MURDERERS, DRUGS AND CORRUPTION - Achmad Musyahid; Abu Sahman Nasim; Samsidar Jamaluddin (Bajang Institute, 2022)
This study aims to analyze the correlation between the death penalty for murder, narcotics, and corruption (a legal approach to jinayah, qishash, hudud, and ta'zir), and aims to look more deeply into the implementation of punishments that use a legal basis or arguments that are general in nature and specific argument. This research uses descriptive qualitative. Data were collected through interviews, observation, and documentation. This study uses data analysis techniques, which consist of stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that legal settlements from the Juridical-Empirical study include makers, dealers, sellers and buyers as well as users, as well as victims of the same status before the law, because they both violate the law, they must be sentenced to death, in the context of crimes against the loss of human life. , in this case the similarity of the punishment of Qishash with the Criminal Code is the same, as in the case of intentional murder that is not condoned by the victim's family. Therefore, the death penalty of Qishash only applies if the intentional killing that is not condoned by the victim's family, as well as corruption of humanitarian funds can be punished by death